Understanding Voice Behavior in Private Healthcare - Eugene Dearuli Marissanti Tindaon (Proceedings of the 1st International Conference on Social Science (ICSS), 2025)
Voice behavior refers to behavior that proactively challenges the status quo and seeks to improve constructive changes. Voice behavior in healthcare is essential for improving patients' conditions and organizational performance. The current study aimed to understand the differences in voice behavior in private healthcare hospitals A and B. This study was conducted through quantitative research, using purposive sampling. Data were collected through an online survey via Google Forms from two private healthcare institutions in Medan. Using SPSS, the researcher compared differences in voice behavior in the mean scores between the two groups. The results of this study depicted differences in voice behavior in healthcare. The data were normally distributed in this study. The tables of voice behavior in Hospital A was higher than Hospital B. This result should be affected by environmental factors such as hospital type, leadership, and management. These findings will contribute to healthcare and organizational behavior.